A fuzzy cognitive mapping approach to scenario development in the South African mining industry - Ackermann, Christiaan (My University, 2018)
The South African mining industry is faced with real challenges that have been devastating in the past. Prolonged labour unrest, regulatory uncertainty, and the aftermath of a global recession which saw commodity prices plummet have impacted on the economy in long lasting ways. Due to these local and global influencers mining executives are now more than ever faced with a critical question: “What does the future of South African mining look like?” Scenario planning, a subset of strategic foresight, is geared towards answering this question by defining the future through multiple lenses and developing robust strategies that cater for more than one version of the future. Mining executives typically develop future scenarios qualitatively, from expert views, but there is a need to develop data-driven scenarios due to the speed and depth of complexity that can be gained. Also, an understanding of what the main industry components and drivers are is required. Therefore, this consulting project develops a systemic view of the South African mining industry, making use of a Fuzzy Cognitive Map, to provide mining executives with a data-driven scenario planning toolkit. The Fuzzy Cognitive Map defines nodes and interrelationships from existing research and is converted into a quantitative model, using an adjacency matrix. Data was collected from 73 South African mining executives to calibrate the model’s causal relationship weights between nodes, and therefore has a high level of credibility. The most sensitive drivers are determined and two scenarios with expected outcomes are used to validate the model. Once validated, the model can now be used by mining executives to develop any other future scenarios within the South African mining industry. Preparing for divergent futures ensures robust strategies are pursued, which provide a competitive advantage in a tough industry. The data-driven scenario planning methodology proposed in this project allows for the development of - 2 - scenarios that are richer in complexity, quick to develop and analyse, and rooted in data, enhancing the strategic planning capability for South African mines.
MBA
Keywords: Mineral industries -- South Africa. Entrepreneurship -- South Africa. Strategic planning -- South Africa.